Improving performance-limited interference system with coordinated multipoint transmission - Aini Syuhada, Md Zain; Abid, Yahya, Dr.; Mohd Fareq, Abd. Malek, Dr.; Normaliza, Omar (Malaysian Technical Universities Network (MTUN), 2013)
Malaysian Technical Universities Conference on Engineering and Technology (MUCET) 2012 organised by technical universities under the Malaysian Technical Universities Network (MTUN), 20th - 21st November 2012 at Hotel Seri Malaysia, Kangar, Perlis, Malaysia.